Unexpected Artifact – A Modding Interface Design - Arminda Guerra Lopes (Interaction Design and Architecture(s), 2018)
Human Computer-Interaction (HCI) has been handled in different ways, which permittedtointerpret the theories, methods and practices according the chosen approach. Some considerations are presented about HCI approaches over the years, and the adopted pedagogical tactics to teach HCI disciplines is described. HCI was taught following the method of teaching / learning pointed to student-centered, supported by incentives for self-learning and integration of knowledge, preparing students for lifelong learning. The student was confronted with a set of theoretical and practical problems, based on real cases, for which they needed to present solutions. The attitude towards the students was challenging them to deal with creativity and how it was affected/supported by technology. The case that we describe in this paper concerns an artifact – a microwave –, which was modified to function differently from what it was built for. We present an example case where students were free to demonstrate their creativity and develop an artifact based on the concept of modding.